Playing three color light's out with Langton's turmite. (15th June 2016) - Arangala, Crista; Brien, Michael O'
Abstract : Light switching games are both popular and well studied. This article introduces a cellular automaton called Langton's turmite to several different light switching scenarios and discusses when Langton's turmite can solve these games. © 2016 Wiley Periodicals, Inc. Complexity 21: 243–248, 2016